2014
DOI: 10.1186/s12964-014-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium is the switch in the moonlighting dual function of the ligand-activated receptor kinase phytosulfokine receptor 1

Abstract: BackgroundA number of receptor kinases contain guanylate cyclase (GC) catalytic centres encapsulated in the cytosolic kinase domain. A prototypical example is the phytosulfokine receptor 1 (PSKR1) that is involved in regulating growth responses in plants. PSKR1 contains both kinase and GC activities however the underlying mechanisms regulating the dual functions have remained elusive.FindingsHere, we confirm the dual activity of the cytoplasmic domain of the PSKR1 receptor. We show that mutations within the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 25 publications
2
52
0
Order By: Relevance
“…Interestingly, prior work with Arabidopsis demonstrated that supplying physiologically relevant concentrations of calcium inhibited PSKR1 kinase activity, while enhancing its GC activity in vitro. These findings suggest that calcium acts as a PSKR1 bimodal switch between the overlapping kinase and GC activities (Muleya et al, 2014). A similar protein structure with dual kinase/GC activities has previously been reported for At-BRI1 (Kwezi et al, 2007) and for Arabidopsis wallassociated kinase-like 10 (Meier et al, 2010), with similar predictions for other kinases.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, prior work with Arabidopsis demonstrated that supplying physiologically relevant concentrations of calcium inhibited PSKR1 kinase activity, while enhancing its GC activity in vitro. These findings suggest that calcium acts as a PSKR1 bimodal switch between the overlapping kinase and GC activities (Muleya et al, 2014). A similar protein structure with dual kinase/GC activities has previously been reported for At-BRI1 (Kwezi et al, 2007) and for Arabidopsis wallassociated kinase-like 10 (Meier et al, 2010), with similar predictions for other kinases.…”
Section: Discussionsupporting
confidence: 82%
“…When isoleucine takes the place of glycine at position 989, it orientates itself towards an opposing β‐sheet causing increased strain with reduced structural flexibility and also increased the overall hydrophobicity in a compact region at the rear of the protein (Figure b). Such changes may account for the reduced GC activity of the BRI1 815–1196 G989I as structural flexibility in particular is an important feature for multi‐functional proteins to allow the switch from one activation state to another as occurs with PSKR1 (Muleya et al ., ). Notably wild‐type BRI1 has strong autophosphorylation activity resulting in heavily phosphorylated recombinant protein whereas both BRI1 815–1196 Y956F and BRI1 815–1196 G989I being ‘kinase dead’ mutants lack phosphorylated residues (Xu et al ., ; Oh et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The superimposed extracted mass chromatograms of m/z 346.06 [M+H] + ion of cGMP all have the corresponding product ion at m/z 152.06 [M+H] + and this confirmed the presence of cGMP in the reaction mixtures of the respective recombinant BRI proteins (Figure b, c). Similar amounts of cGMP are generated by the recombinant cytoplasmic domain and the full‐length PSKR1 (Kwezi et al ., ; Muleya et al ., , ). It is noteworthy that a recently characterized adenylate cyclase from Arabidopsis (AtKUP7) also has activity resembling that of plant GCs (Al‐Younis et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Muleya et al . ). The binding of Ca 2+ /Calmodulin to PSKR1 is required for receptor activity (Hartmann et al .…”
Section: Introductionmentioning
confidence: 99%